Characterization of Learning Assessment in a University with a Distance Modality: The Case of Universidad Estatal a Distancia (UNED), 2017 - Calderón Badilla, Yency (2020)
The evaluation of learning is developed according to the guidelines and institutional regulations of an educational entity and is a reflection of a pedagogical and didactic strategy. For this reason, in 2017, a qualitative research was carried out with a comparative analysis of several institutional documents of Universidad Estatal a Distancia of Costa Rica. Guiding questions were stated in relation to the evaluation of learning: How should the evaluation of learning be?, who does it serve?, what is its planning and function?, and what type of evaluation is given? Although coincidences were found in the self-assessment and peer assessment strategies, there is no single institutional concept regarding the evaluation of learning, but it is at the service of the students with a guiding, preventive, and corrective feedback purpose. However, agreement is required on the characteristics and attributes that are expressed in the regulations with the planning of the evaluation, especially in the mechanisms of control for expected compliance. In a distance education model, the approach of evaluating to learn seems to be more relevant, given that it includes diagnostic, formative, self-regulated learning, and summative evaluation through alternative strategies that enable self-regulation of the students.